Design and Validation of Software for the Training and Automatic Evaluation of Music Intonation on Non-Fixed Pitch Instruments for Novice Students - Jesús Tejada; María Ángeles Fernández-Villar (Education Sciences, 2023)
Music education, whether professional or amateur, includes learning musical instruments. Intonation is a critical factor in their training. The main objective of this research work is the design and validation of online educational software for the real-time training and evaluation of intonation in non-fixed pitch musical instruments, such as fretted string instruments (violin, viola, and cello) and brass instruments (trumpet, horn, and trombone). This software is intended to create a practice artefact for novice music students. A design sciences research methodology is adopted to achieve a product tested for functionality and usability. Novice students carry out the validation phase through a study consisting of previous practice with the software and the administration of a questionnaire with open-ended items grouped in technical-didactic, emotional, and overall dimensions, plus two additional questions. The results show evidence that the software was well received, confirming previous studies on the design and validation of educational music education software.